In the flesh series 1-2 - Butt, Edmund 1968- (BBC, 2014)
"Set after a zombie uprising, treated zombies are rehabilitated back into society." [bbc.co.uk]
Bildformat 2.35:1
Orig.: Großbritannien 2013 - 2014